Insecurity and National Development: Nigeria at a Crossroad (Global Journal of Human-Social Science, 2021)
Insecurity has become the defining characteristic of Nigerian political scene, especially since the return to democracy in 1999. Its rising wave in the recent times has taken a very perilous dimension which is fast decelerating her development and threatening the corporate existence of the country as a nation. Available data on the level and dimensions of insecurity in Nigeria reveals an increase over time. Since the emergence of nascent democracy, major cities and towns have become flashpoints of violent clashes, kidnapping, assassination, rape, hijacking, sabotage, insurgency and looting. The curiosity to x-ray the dastard effects of insecurity on Nigeria's development informed this study. Content analysis was adopted for the paper, and relevant journals, texts and other academic documents were used. The paper revealed that Nigeria's national security is at crossroad and the effect is dastardly felt on her development. Corruption, injustice, high level of inequality, poverty and religious intolerance are revealed as the impetuses that heighten the tension of insecurity in Nigeria. The paper, amongst others, recommended a holistic overhauling of Nigeria's security architecture, equality in the distribution of national wealth and tolerance.